Modification of lignites via low temperature ionic liquid treatment - Cummings, J.; Tremain, P.; Shah, K.; Heldt, E.; Moghtaderi, B.; Atkin, R.; Kundu, S.; Vuthaluru, Hari (Elsevier, 2017)
© 2016 Elsevier B.V. Two lignite samples (150–212 µm) were treated with four ionic liquids (ILs); 1-butylpyridinium chloride ([Bpyd][Cl] ), 1-ethyl-3-methylimidazolium dicyanamide ([Emim][DCA] ), 1-butyl-3-methylimidazolium chloride ([Bmim][Cl] ) and 1-butyl-3-methylimidazolium tricyanomethanide ([Bmim][TCM] ) at 100 °C for 3 h to establish the utility of ILs for lignite pre-treatment in conversion processes. ILs are room temperature molten salts that have remarkable physical and chemical properties including high thermal and electrochemical stabilities, low vapour pressures and, critically for this work, the capacity to solubilise a diverse range of materials. Thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), and optical microscopy were employed in this study to gain insight into the physical and chemical interactions occurring between lignite and ILs at low temperatures. The FTIR results indicate that the majority of the ILs employed were able to break apart the macro-structure of coal resulting in an increase in short chain aliphatic hydrocarbons. Additionally, FTIR analysis revealed a significant decrease in the presence of COOH and CO groups for lignites treated with [Emim][DCM] . The TGA data revealed that the IL treated lignites had significantly lower devolatilisation temperatures than the untreated lignite, indicating an increase in lower molecular weight species after treatment. Microscopy showed a sizeable decrease in particle size after IL treatment due to fragmentation, and these coals appeared to be considerably swollen. Analysis of the recovered ILs showed no denaturing after the treatment process, indicating their recyclability potential in the treatment process.